Prevalencia epidemiológica de Brucella abortus en la parroquia Eloy Alfaro del cantón Chone - Bravo Morán, Ángela Leopoldina (2022)
The purpose of the investigation was to evaluate the epidemiological prevalence of Brucella abortus in the Eloy Alfaro parish in Chone canton, where a sampling of 414 cattle older than six months was carried out, for the collection of samples, 15 herds were selected that were divided into three categories (small, medium and large), of which 5 were taken for each category, where samples were taken from 13 animals in small herds; 23 in medium and 47 samples in large herds, the study variables analyzed through the surveys (age/months), grouped into three categories (I:6-24); (II:25-60); (III:>60); sex (female-male); body condition (1-5) and vaccination status against bovine brucellosis (yes-no), where 5 ml of blood were taken by venipuncture between the sixth and seventh intercoccygeal space, centrifuged to obtain serum and apply the techniques (Rose Bengal - Slow seroagglutination in tube (SAT)). A prevalence of 5.8% corresponding to Rose Bengal and 8.5% to SAT was obtained, which determined the infectious phase of the disease. Highly significant differences (P<0.05) were found between sex, body condition and Brucella abortus vaccine. It is concluded that Brucella abortus is present in said parish with moderate prevalence, where the presence of other species (87%), absence of sanitary registration of introduced animals (33%), incorrect handling of manure (67%), ignorance (47%) and non-vaccination (87%) are elements that could increase the spread of the disease as evidenced in the investigation.